Case Report: Ictal hypersalivation: a stereoelectroencephalography exploration - Ouchida, Sumika; Nikpour, Armin; Wilson, David Neville; Fairbrother, Greg (Frontiers in Surgery, 2025)
Epilepsy is a chronic neurological condition with various etiologies, and recurrent unprovoked seizures characterize it. Hypersalivation is a recognized symptom of insular-opercular epilepsies. A wide range of symptoms can occur during a seizure, including hypersalivation, autonomic responses, oropharyngeal sensations, visceral sensations, somatosensory disturbances, and emotional manifestations. In this case study, we examine a unique scenario of a patient who experienced predominantly salivary seizures. Hypersalivation, pill-rolling movements, and lip-smacking characterized these seizures. Importantly, the patient became seizure-free after undergoing radiofrequency thermocoagulation (RFTC) with the assistance of Stereoelectroencephalography (SEEG). Our discussion will focus on the treatment approach involving SEEG-guided RFTC and the careful identification of the brain cortex responsible for triggering excessive salivation during seizures.